Holocene palaeogeographical recontruction oof the western part of Naxos island (Greece). - Evelpidou, N.; Pavlopoulos, K.; Vassilopoulos, A.; Triantafyllou, M.; Vouvalidis, K.; Syrides, G. (Quaternary International, 2012)
Naxos Island is situated in the Cycladic plateau (middle Aegean Sea) and consists of concaved beach zones separated by small headlands. This study investigates the diachronic palaeo-shoreline shift due to the sea level change and its effect to the palaeo-environmental evolution of the western coastal part of Naxos Island during the Late Holocene. For this purpose, six boreholes were drilled and dated using radiocarbon techniques. The associated geomorphological, sedimentological and paleontological investigation concluded that during Late Holocene, the embayments of Naxos western coastal part were frequently exposed, and their communication with the sea was not perennial. The coastal area was wider with many active lagoons and embayment changing from shallow marine environment to coastal environment frequently alternating to brackish mesohaline one. The former sea-level position in western Naxos island should be between −1.5 m and −2 m during the last 2000 years, which may partly reflect eustatic processes and partly a gradual or coseismic land subsidence.